Assessment Of Antimicrobial Activity Of New Sulphanylamide Derivatives Against Multidrug Resistant Urinary Tract Pathogens - MRS. GAURI DEVASTHALE; DIVYA NAIR; JHILMIL GHOSHAL (International Journal of Pharma and Bio Sciences, 2012)
Seven newly synthesized sulphanylamide derivatives were tested in terms of antimicrobial activity individually, in combination with metals and in combination with each other against nosocomial pathogens isolated from urine samples. Among the tested compounds STZ exhibited the strongest inhibition. Antagonistic effect was observed when this compound was combined with metals. Synergistic effect was observed when it was combined with other sulphanylamide derivatives. This study may assist to propose an alternating, promising leading compound for the development of new antimicrobial agents against taxing multidrug resistant UTI pathogens. Another conclusion that can be drawn is that whenever these compounds are formulated into drugs the formulation should be devoid of metals since the drug interaction that was observed in this combination was that of Antagonism.